Preeklampsi-eklampsi sebagai Faktor Dominan yang Berpengaruh terhadap Kejadian Asfiksia Neonatorum (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2018)
Background: Asphyxia neonatorum in Metro city is the main cause of infant mortality. Purpose: This study aims to determine the most dominant factors that influence the incidence of neonatal asphyxia.. Methods: The design of this study was a case control study with retrospective direction dimensions. The case was neonatal asphyxia in newborns at Mardi Waluyo Metro City Hospital, which was sourced from medical records. Case and control groups with a ratio of 62: 62 (1: 1). Data collection using questionnaire check list form. The research variables analyzed consisted of asphyxia neonatorum (dependent variable), pre-eclampsia / eclampsia, hypertension, pregnancy anemia, antepartum hemorrhage, history of poor obstetrics and delivery of action (independent variable). Data analysis used multivariate analysis with multiple logistic regression tests. Results: Based on the final multivariate model, the pre-eclampsia-ecalmpsia factor was the most influential determinant of neonatal asphyxia (p = 0.005; ORadjusted = 9.1924; 95% CI 1.924-43.934), after being controlled by other variables. Conclusion: The incidence of pre-eclampsia / eclampsia in pregnant women statistically provides a 9 times chance of babies born asphyxia neonatorum. Prevention efforts for preeclampsia / eclampsia with regular pregnancy care are needed, so that the incidence of neonatal asphyxia can be prevented.